THE COMPARISON OF MICROSTRUCTURAL ARRANGEMENT OF NORMAL RETINAL LAYERS IN RAT AND HUMAN - Пальтов, Е.В.; Mateshuk-Vatseba, L.R.; Кривко, Ю.Я. (World of Medicine and Biology, 2015)
The purpose of present investigation was the study fundamental questions concerning the comparison of microstructural component layers of the retina of rat and human normal. The task has been achieved through the use of techniques of histological visualization of the retina layers. Histological preparations were prepared by the conventional method using dyes, which include hematoxylin, eosin and (Azan) in Heidenhain method. This information will enable the future to form the basis for post-mortem morphological pattern of rat retinal layers at normal with the elements of topographic comparing it with the layers of the human retina at normal. This will make it possible in the future to form a morphological substrate of normal with the next possibility of comparative characteristics of rat retinal elements at the influence of the various pathological conditions and in earlier and later terms of the correction.